(untitled) (Pragya Darshan प्रज्ञा दर्शन, 2023)
The juvenile justice system identifies youth in conflict with the law as different from the adult criminal population. The Correctional and re-integrative approach forms the basis of a good juvenile justice system. The rationale for such interventions remains to identify risk factors and protective factors for delinquency. History of victimization has been recognized as one of the risk factors for juvenile delinquency. In this context, a cross-sectional study was conducted with 160 adolescents (with a history of juvenile delinquency) residing in Child Correction Homes of Bhaktapur and Kaski districts to study the history of victimization its effect on behavioral and emotional problems. Nepalese versions of the Reduced Item Juvenile Victimization Questionnaire (JVQ) and Strength and Difficulty Questionnaire (SDQ) were used for the study. Of the participants (N=149), 93.96 % reported at least 1 victimization and 79.19% reported lifetime exposure to 3 or more different types of victimization. Total score in JVQ was a significant predictor for Hyperactivity, Emotional Problems, Peer Problems, and Total Difficulty Score of SDQ. These findings point toward the need to further study these aspects of delinquency in the Nepalese context.